Exploring Translanguaging Practices in Indonesian Education - Nurhayati (Universitas PGRI Adi Buana Surabaya, 2023)
The aim of this paper is to elucidate a comprehensive perspective on translanguaging practices in Indonesian education by reviewing empirical literature published in scientific journals. There have been debates on how different languages should be treated in a language learning class especially in EFL classroom context, where students have limited access to target language use and exposure outside the classroom. This study involved 5 ELT teachers and 10 secondary students by collecting data through observations, interviews, and questionnaire. Teachers and students have the benefit of translanguaging practices in EFL classrooms, yet it should be taken into account that L1 should be adopted judiciously. They translanguage using English, Indonesian, and local languages. They have voiced their agreement to the implementation of translanguaging as pedagogy since it positively impacts EFL teaching and learning. However, few teachers have contrasting views about this voice. Future research should focus on investigating translanguaging through experimental research design or pedagogical intervention in EFL classrooms whose students are coming from multiple linguistic backgrounds. The implications of the practice of translanguaging at Indonesian Education are effective and optimal to help students as a new strategy in learning English as foreign language because it can be used to motivate and analyze students' problems in mastering English as a foreign language.